Integrated vermin-AD technology in managing waste in Pulau Tioman; promoting green technology in managing organic wastes via vermicomposting - Abd Aziz, Nor Azwady; Sulaiman, Siti Rohani; Idris, Azni; Mustafa, Muskhazli; Omar, Hishamuddin; Wan Ab. Karim Ghani, Wan Azlina; Wan Chik, Burhanuddin; Ishak, Nur Ain (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2014)
Vermicomposting is proven to be an effective way to convert large quantities of organic waste into a highly value-added product, vermicompost. It is a green technology of composting organic materials that involves the joint actions of microorganism and earthworm. The present project was aimed to transfer knowledge of vermicomposting to the Tioman Development Authority (TDA) personnel, to create awareness among the local people in managing the organic wastes in a more environmental-friendly manner, and the pilot vermicomposting plant is projected to serve as reference centre and a new tourist product in Pulau Tioman. The knowledge transferred to the local authority via workshop and on-sitetraining includes bedding preparations, maintenance, monitoring the system and harvesting the vermicompost. One vermicomposting pilot scale set-up(approximately 50kg/day) has been established in Tekek to initially demonstrate vermicomposting process effectively, and later serves as the reference centre.